Clinical and pathological analyses of epithelioid hemangioma in sixteen cases - Yao-xin XIE; Wei-fen WU; Yi-fang ZHONG (editoiral office of Journal of Diagnosis and Therapy on Dermato-venereology, 2020)
Objective: To investigate the clinical and pathological features of epithelioid hemangioma (EH). Methods: Retrospective analyses were performed on the clinical and pathological data of sixteen patients with EH, and related literatures were reviewed. Results: Sixteen patients, including 8 females and 8 males, were aged 45.44±12.52 years, with 3-month to 12-year history of EH. All subjects showed typical clinical and histopathological features.The main manifestations of the skin were red to dark red papules and nodules, some of which were accompanied with pruritus and erosion. Involvements of the head, ears, and vulva were 10, 5 and 1 cases, respectively. Five cases showed single skin lesion, and 11 cases with multiple skin lesions. Histopathological features included typical vascular proliferation, thickened vessel walls, epithelioid-like endothelial cells protruding into the lumen, and perivascular infiltration of large amounts of lymphocytes and eosinophils. Conclusions: Epithelioid hemangioma is rare. The diagnosis should be based on both clinical and pathological features. Enhancing awareness of this disease would be helpful to avoid misdiagnosis and improper treatment.